Sanksi Pengabaian Hak Alimentasi Anak: Perspektif Fiqh dan Perundang-Undangan Indonesia - Alfian Qodri Azizi (Jurnal Iqtisad, 2020)
Abstract Fulfilment of children's alimentation right is a medium to apply the vision of marriage that functions actively-offensively protecting generation (ḥifẓ an-nasl). However, there are still many cases neglecting children's alimentation right in marriage or after divorce. This is due to some understanding of the classical mazhab of fiqh that children's alimentation right not be a father's debt, the obligation of child's alimentation expired if not given in the past and because also the people assume that the husband's obligation to give a child's alimentation only occurs when there is still a marriage. So that when the divorce happens it means the obligation of a child's alimentation has ended by the father to his child. from this legal problem, the author wants to examine how the juridical-normative rules for granting children's alimentation right and the sanctions if father ignore the children's alimentation right? This study uses a comparison method between Fiqh and the Act in Indonesia. The result is the Act and Fiqh have governed the procedures for granting children's alimentation right. However, sanctions governing neglect of granting children's alimentation right in fiqh are only found in the mazhab Hanafi, but in the Act found strict sanctions as a preventive measure and as well as a deterrent effect, so that a person does not neglect children's alimentation right